Pengaruh Cryotherapy, Ultrasound dan Strengthening Exercise pada Post Rekonstruksi Anterior Cruciate Ligament Fase I: A Case Report - Tiara Fatmarizka tiara; Reza Perdana Kusuma reza (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
The ACL is a ligament in the knee that has the main function of stabilizing the knee in preventing the movement of the tibia from sliding forward and controlling movement during knee rotation. Rupture is the tearing of tissue caused by trauma. A tear in the Anterior Cruciate Ligament caused by direct or indirect trauma to the knee. Direct trauma occurs due to direct contact with the knee when the knee moves laterally or anteriorly, causing the ligament to tear. This study aims to describe the effect of physiotherapy intervention in the form of modalities given for pain management, joint range of motion and functional ability after ACL reconstruction. Description The patient is 31 years old with a history of falls in the past 3 years. The patient feels pain in the area around the incision, has not been able to move the leg normally, the leg cannot be bent maximally, and the leg feels heavy and sluggish. The patient comes to the clinic using an assistive device (elbow crutches) with a non-weight bearing gait pattern. Results and Discussion: The intervention patients were given in the form of cryotherapy, ultrasound, and strengthening exercises in the form of Quadriceps Setting, Hamstring Setting, For Way Hip Exercise, Qalm Shell Exercise, and Ankle Theraband Exercise. The results showed a decrease in pain in the incision and movement area, a decrease in edema, an increase in the range of motion of the joint, and an increase in the strength of the muscles that move the knee joint. The administration of cryotherapy, ultrasound, and strengthening exercises have been shown to reduce pain, increase joint range of motion, increase muscle strength, and reduce edema in patients after phase 1 Anterior Cruciate Ligament (ACL) reconstruction.